SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KUALITAS PELAYANAN PADA MALANG DORM HOSTEL MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Purnamasari, Putri Indah; Marisa, Fitri (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
The expanding world of the hospitality industry makes the company have to compete tightly to keep its business. Quality of service from a company affects the level of customer satisfaction, If the better the quality of service then the level of customer satisfaction is higher. Decision support system to determine service quality at hostel dorm hostel using SAW method can help companies evaluate the quality of service that has been given. The results of the evaluation can be used to determine policies relating to efforts to improve service quality. The results obtained from the calculation of the weight of the criteria assessment with the Fuzzy Simple Additive Weighting (SAW) method succeeded, thus obtaining the VAR score (the result of the assessment at Malang Dorm Hostel exceeded the 4-5 star rating of the customer is good-very good.